The human anti-ganglioside GM1 autoantibody response following traumatic and surgical central nervous system insults. (August 2022) - Schneider, Lonnie; Rezaeezade-Roukerd, Maryam; Faulkner, Jenna; Reichert, Ethan; Abou-Al-Shaar, Hussam; Flis, Alexandra; Rubiano, Andres M.; Hawryluk, Gregory W.J.
Abstract: Predictors of the central nervous system (CNS) directed autoantibody response after acute CNS injury are poorly understood. We analyzed titers of IgG and IgM autoantibodies to ganglioside GM1 in serial serum specimens collected from human patients following acute spinal cord injury (SCI), traumatic brain injury (TBI) and brain tumor resection. We also assessed putative predictors of the autoantibody titers. We enrolled 19 patients with acute SCI, 14 patients with acute severe TBI, and 19 patients undergoing brain tumor resection. We also enrolled 25 control subjects. Some SCI, TBI and tumor patients exhibited elevated IgG titers as compared with control values; some SCI and TBI patients exhibited an acute peak in IgG titers, most commonly 14 days after insult. Some clinical and radiographic measures of injury severity correlated with IgG titer elevation in SCI and TBI patients but not tumor patients. Our study demonstrates that diverse CNS insults are followed by increased IgG autoimmune antibody titers to the CNS antigen ganglioside GM1, however the response inherent to each insult type is unique. IgG autoimmune antibody titers to GM1 merit further study as a biomarker of traumatic injury severity that can be measured in delayed fashion after CNS insult. These human data help to inform which patients with CNS insults are at risk for CNS-directed autoimmunity as well as the time course of the response. Highlights: Different CNS insults exhibit unique autoantibody responses. Ganglioside GM1 IgM did not show promise as a biomarker. GM1 IgG demonstrated a delayed rise in some patients with peak values at 14 d. Injury severity was the best predictor of ganglioside GM1 IgG titer elevation.